PENDIDIKAN LINGKUNGAN HIDUP DALAM UPAYA PELESTARIAN FUNGSI HUTAN LINDUNG DI BAJAWA UTARA - Ferdinandus Samri (STKIP CITRA BAKTI, 2021)
ABSTRACT The objective of the research is determining the link of Knowledge about environment of societies and the effort of conservation to take care of conservation forest function. The societies where lived nearby forest conservation in sub region of Borong needs to increase their knowledge about environment. Base on the data analysis that stemmed from the object of this research found: First, The fact that people whose lived in around / closed to conservation forest area have been owned knowledge about environment. Generally their knowledge about environment stemmed from formal education and also non formal which obtained by training and sharing of knowledge about environment by the government of East Manggarai region. Beside that, their knowledge about environment they stemmed from traditional knowledge form which endowment of their ancestor. Second, the conservation effort to take care forest conservation function in sub region of Borong was conducted by the government in cooperative with various inter technical instance; and Third, the effort of society to take care of conservation forest function nowadays is better then before, they have knowledge about environment, it’s present by their eagerness to join in all the activities for the sake of conservation forest function in the future.